DOCKING OF TYROSINASE CICLOARTANE INHIBITORS - Pablo A. GUTIÉRREZ (Universidad de Antioquia, 2009)
Berenjenol (21:24-epoxy-24-methyl-cicloartane) isolated from leaves of Oxandra cf. xylopioides (Annonaceae), and its synthetic derivatives Berenjenol-3-acetate and 3-Oxoberenjenol are tyrosinase inhibitors (EC 1.14.18.1). These compounds are triterpenoids type cycloartanes, whose structure-activity relationship has been studied on similar compounds. However, the mechanism of inhibition of these molecules is not well understood. This paper present the results of a docking study between Berenjenol and its derivatives on tyrosinase enzyme that provides a rational framework for understanding the activity of these compounds. According to this work, Berenjenol acts as a competitive inhibitor of tyrosinase through interactions with Ile42, Met43 Arg55, Trp184, Asn191, His194, Val195, Ala202, Met201 and Thr203.